The Concept of Taskhīr Al-Baḥr: Blue Economy Efforts to Advance the Economy of The Ummah - Abdul Haqqi; Ahmad Khaerussalam (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2025)
This study explores the concept of taskhīr al-baḥr (subjugation of the sea) in the Qur’an and its implementation within the framework of the blue economy to promote the economic development of the Muslim community in Indonesia. It analyzes Surah an-Nahl [16]:14, which implies a mechanism for utilizing the sea and aquatic resources, and integrates it with the blue economy concept. The study finds that the concept of taskhīr al-baḥr produces an effective and efficient mechanism for the utilization of the sea and its resources through three aspects: the use of marine life as food, pearls as ornaments, and ships as a means of transportation. The integration of the taskhīr al-baḥr concept within the blue economy framework has the potential to advance the community’s economy through efficient resource utilization, job creation, and a balanced approach to production and consumption. This research contributes to the development of a model for marine resource management based on Qur’anic values and blue economy principles, which can be implemented in Indonesia’s marine policy.